6q-4+8q-2=20+(6-4)

Simple and best practice solution for 6q-4+8q-2=20+(6-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6q-4+8q-2=20+(6-4) equation:


Simplifying
6q + -4 + 8q + -2 = 20 + (6 + -4)

Reorder the terms:
-4 + -2 + 6q + 8q = 20 + (6 + -4)

Combine like terms: -4 + -2 = -6
-6 + 6q + 8q = 20 + (6 + -4)

Combine like terms: 6q + 8q = 14q
-6 + 14q = 20 + (6 + -4)

Combine like terms: 6 + -4 = 2
-6 + 14q = 20 + (2)
-6 + 14q = 20 + 2

Combine like terms: 20 + 2 = 22
-6 + 14q = 22

Solving
-6 + 14q = 22

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 14q = 22 + 6

Combine like terms: -6 + 6 = 0
0 + 14q = 22 + 6
14q = 22 + 6

Combine like terms: 22 + 6 = 28
14q = 28

Divide each side by '14'.
q = 2

Simplifying
q = 2

See similar equations:

| 26=(x+2) | | 5x-3=10-2x | | x^3+2x-63x= | | 16-x+36=x+45 | | 7r+6(r-2)=4r+10(2r+1) | | 45x^2+93x+30= | | 5x+1=7x+10 | | 3x-1=2x-4+2x-3-2 | | 35x^2+38x+8= | | 9x/25=88 | | x-16=36+x+45 | | y^4-13y^2=-36 | | x^3+6x^2-16x= | | 33=3x-28+3x-30+x | | x+16-x=x+36+x-45 | | 4v-2+8v=6 | | -6+v=-9 | | 6(-7)= | | -3z+8+(-22)=-12 | | 9x+25=113 | | 9x+25=63 | | 6=9(h+2) | | -2y+5+5y=19 | | (-6x^8y)(x^7y^3)= | | (-3-2i)-(12-5i)= | | 19-13p=-17p-15 | | z(3z+2)=(z+2)(z+2) | | 1/9x=3 | | 72+4-19c=36 | | 5-1/3(b-6)=4 | | 2x-1=3x+99 | | 26+x=x+23+12-14+x |

Equations solver categories